Structure and Sequence Determination of Amino Acids in Protein Molecules - Aminzai, Mohammad Tahir (Journal of Natural Sciences – Kabul University, 2023)
Amino acids are the building blocks of all peptides and proteins, which determine many of their important physiological properties. Amino acids help break down food, grow and repair body tissue, make hormones, provide energy, maintain healthy skin, hair, and nails, build muscle, and boost your immune system. In nature, there are over 500 distinct amino acids, however only 20 of them are involved in protein synthesis. Identifying the amino acid sequence of a protein or peptide provides useful information for understanding its structure and physiological functions. In this review article, different chemical methods such as Edman and Sanger degradation, as well as different chemical reagents such as ninhydrin, carboxypeptidase, and hydrazine, to identify the composition and sequence of amino acids in protein molecules, have been reviewed.